Risk Factors Associated With Social Media Addiction: An Exploratory Study - Zhao, Jin; Jia, Ting; Wang, Xiuming; Xiao, Yiming; Wu, Xingqu (Frontiers in Psychology, 2022)
The use of social media is becoming a necessary daily activity in today’s society. Excessive and compulsive use of social media may lead to social media addiction (SMA). The main aim of this study was to investigate whether demographic factors (including age and gender), impulsivity, self-esteem, emotions, and attentional bias were risk factors associated with SMA. The study was conducted in a non-clinical sample of college students (N = 520), ranging in age from 16 to 23 years, including 277 females (53%) and 243 males (47%). All participants completed a survey measuring impulsivity, self-esteem, anxiety, depression, social anxiety, loneliness and attentional bias. The final hierarchical regression model indicated significant risk factors for SMA with an accuracy of 38%. The identified set of associated risk factors included female gender (β = 0.21, t = 4.88, p < .001), impulsivity (β = 0.34, t = 8.50, p < .001), self-esteem (β = 0.20, t = 4.38, p < .001), anxiety (β = 0.24, t = 4.43, p < .001), social anxiety (β = 0.25, t = 5.79, p < .001), and negative attentional biases (β = 0.31, t = 8.01, p < .001). Finally, a discussion of the results is presented, followed by corresponding recommendations for future studies.